UTILIZING YOUTUBE AS A MATERIAL FOR ICT LEARNING AT ELEMENTARY SCHOOL DURING THE COVID-19 PANDEMIC - Maya Nurjanah; Andi Prastowo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the outbreak of COVID-19, which was very influential in education and other aspects of life. As a result, the government closed the schools and made a rule to implement online learning (in the network). Thus, we needed a solution or alternative to solve these problems. In the midst of the COVID-19 pandemic, it was recommended to use innovative online learning media, especially for elementary school students, to increase their motivation while studying at home. Not all online learning methods could be used in the ICT learning process, which was related to practical activities. YouTube-based learning media was used in the online learning process for ICT subjects. The purpose of this study was to reveal the procedure of utilizing YouTube for online learning in elementary schools. This study used a library research method, while the data sources used in the study were in the form of journals and books related to the research title. The data were collected through the documentation of several research sources, either from journals or books. Then, they were processed and analyzed to draw conclusions. The results of the research found that utilizing YouTube as a teaching material in ICT learning was very much needed by educators in today's situations.